Comparative study of biological and metabolic indicators in males and females Pseudocurimata boulengeri of lotic ecosystems - Méndez-Martínez, Yuniel; Pallo-Molina, Estefanía; Fernández-Escobar, Angel; Vasco-Mora, Diana (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2023)
With the objective of evaluating different biological and metabolic indicators in males and females Pseudocurimata boulengeri in three ecosystems of Los Ríos, Ecuador, specimens were captured in the areas of Ventana, Quevedo and Buena Fe (60 per area, 180 total), and proceeded to perform the sexing. The following were determined: size, weight, thickness of the head, trunk and tail, as well as the size-weight relationship. Stomasomatic, gonadal, hepatosomatic, vicerosomatic indices and condition factor. Glucose, total protein, cholesterol and triglyceride were also evaluated. A 3×2 factorial arrangement was used. Regression analysis to establish the functional relationship between length and weight. For the morphometric indicators, differences between interactions were shown, although higher values ​​were observed in females regardless of the locality, with a weight of 185 g, a length of 23.43 cm and head thickness that exceeded 6 cm. The biological indices reflected differences between the interactions, thus the hepatosomatic, gonadal, and vicerosomatic indexes were higher for females in the locality of Ventanas with 0.97, 12.76, and 20.04, respectively. For the metabolic indicators, differences were shown between the interactions with greater variability for sex. It was shown that for the morphometric indicators, sex did not prevail. The biological indices were influenced by sex, with superiority for females except the stomasomatic. While metabolic indicators showed variability with respect to areas and sex.